Infection and Rapid Transmission of SARS-CoV-2 in Ferrets - Kim, Young-Il; Kim, Seong-Gyu; Kim, Se-Mi; Kim, Eun-Ha; Park, Su-Jin; Yu, Kwang-Min; Chang, Jae-Hyung; Kim, Eun Ji; Lee, Seunghun; Casel, Mark Anthony B.; Um, Jihye; Song, Min-Suk; et al. (Cell host & microbe, 2020)
The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in China and rapidly spread worldwide. To prevent SARS-CoV-2 dissemination, understanding the in vivo characteristics of SARS-CoV-2 is a high priority. We report a ferret model of SARS-CoV-2 infection and transmission that recapitulates aspects of human disease. SARS-CoV-2-infected ferrets exhibit elevated body temperatures and virus replication. Although fatalities were not observed, SARS-CoV-2-infected ferrets shed virus in nasal washes, saliva, urine, and feces up to 8 days post-infection. At 2 days post-contact, SARS-CoV-2 was detected in all naive direct contact ferrets. Furthermore, a few naive indirect contact ferrets were positive for viral RNA, suggesting airborne transmission. Viral antigens were detected in nasal turbinate, trachea, lungs, and intestine with acute bronchiolitis present in infected lungs. Thus, ferrets represent an infection and transmission animal model of COVID-19 that may facilitate development of SARS-CoV-2 therapeutics and vaccines. [Display omitted] •SARS-CoV-2-infected ferrets exhibit elevated body temperature and virus replication•SARS-CoV-2 is shed in nasal washes, saliva, urine and feces•SARS-CoV-2 is effectively transmitted to naive ferrets by direct contact•SARS-CoV-2 infection leads acute bronchiolitis in infected ferrets The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) rapidly spreads, leading to a pandemic infection. Kim et al. show that ferrets are highly susceptible to SARS-CoV-2 infection and effectively transmit the virus by direct or indirect contact, recapitulating human infection and transmission.